Joint Association of Physical Activity and Sleep Duration with All-Cause and Cause-Specific Mortality: A Prospective Study of 153,866 Mexican Adults - De Moraes-Ferrari, G (Elsevier Ireland Ltd, 2025)
Objective: This study investigated the joint association of physical activity (weekly frequency and duration) and sleep duration with all-cause and cause-specific mortality. Methods: We conducted a prospective cohort study of 153,866 participants from the Mexico City Prospective Study. Cox proportional hazards regression was used to estimate the joint associations of frequency (none, < 1, 1–2, and ≥ 3 times/week) and session duration (none, < 30, 30–60, and ≥ 60 min/day) of physical activity and sleep duration (recommended: 7–9 h/day; below/above recommended: <7 or > 9 h/day) with the risk of all-cause and cause-specific mortality (cardiovascular disease, cancer, and respiratory diseases). Results: Over 15.6 years of follow-up, higher risks of all-cause, cardiovascular diseases, and cancer mortality were observed among participants with: no physical activity and recommended sleep duration; < 1 time/week of physical activity and below/above recommended sleep; and no physical activity and below/above recommended sleep (compared to higher physical activity and recommended sleep duration. Similar positive associations were observed when considering physical activity duration. The highest risks of all-cause, cardiovascular disease, and cancer mortality were found among participants with no physical activity (duration) and below/above recommended sleep duration. Conclusions: Our findings suggest that low levels of physical activity and non-recommended sleep durations jointly increase the risk of all-cause and cause-specific mortality. © 2025 Elsevier B.V.